Understanding Contact Angle Hysteresis The Case of Slippery Micropatterned Biphilic Liquid-Like Surfaces - Hu, Ruiheng (Langmuir : the ACS journal of surfaces and colloids, 2025)
Shedding droplets and bubbles from surfaces is important in a wide range of practical situations, such as keeping windows dry, preventing icing, and heat transfer during nucleate boiling. A challenge for understanding these processes is the influence of pinning in hindering contact line motion. Here, we report the pinning caused by square patterns of hydrophilic microscopic areas within a hydrophobic surface, where both possess ultralow contact angle hysteresis (ca. 3°). The surfaces are created using a new lithographic method to pattern circular areas of a hydrophilic PEG-based slippery covalently attached liquid surface (SCALS) within a hydrophobic PDMS-based SCALS background. We observe that, at low (<35%) or high (>65%) Cassie surface area fractions for one component of the surface, the increase in droplet pinning in roll-off experiments can be described by a strong dilute defect model. In the intermediate range, droplets exhibit contact line faceting, with roll-off angles becoming more scattered. We find that a single parameter a = 0.54 ± 0.04 can be used to fit our data for both cases of the hydrophilic areas regarded as defects within a hydrophobic background and the hydrophobic areas regarded as defects within a hydrophilic background. Finally, we propose an equation for the strength of pinning force per defect as a function of the two contact angles and a defect shape factor. These results are relevant for situations, such as self-cleaning and anti-icing, where pinning of droplets dominates the surface's liquid-shedding properties, or in phase-change-based heat transfer, where the inverse problem is the shedding of bubbles